Vascular Endothelial Growth Factor (VEGF) Family and the Immune System: Activators or Inhibitors? - Cristina Maria Failla; Maria Luigia Carbone; Carmela Ramondino; Emanuele Bruni; Angela Orecchia (Biomedicines)
The vascular endothelial growth factor (VEGF) family includes key mediators of vasculogenesis and angiogenesis. VEGFs are secreted by various cells of epithelial and mesenchymal origin and by some immune cells in response to physiological and pathological stimuli. In addition, immune cells express VEGF receptors and/or co-receptors and can respond to VEGFs in an autocrine or paracrine manner. This immunological role of VEGFs has opened the possibility of using the VEGF inhibitors already developed to inhibit tumor angiogenesis also in combination approaches with different immunotherapies to enhance the action of effector T lymphocytes against tumor cells. This review pursues to examine the current understanding of the interplay between VEGFs and the immune system, while identifying key areas that require further evaluation.